E-212 Pulserider in the treatment of wide-neck bifurcation aneurysms: interim results of the NAPA trial. (4th August 2020) - Spiotta, A; Ebersole, K; Lena, J; Starke, R; De Leacy, R; Puri, A; Yavagal, D; Bohnstedt, B; Rangel-Castilla, L; Cheema, A; Davies, J; de Macedo Rodrigues, K; et al.
Abstract : Introduction: The NAPA study was a prospective, multicenter, single-arm IDE trial of the PulseRider device as an adjunctive treatment in conjunction with coil embolization of unruptured wide-neck bifurcation aneurysms which was electively discontinued for reasons not related to the safety or performance of the device. We report on the available enrollments in NAPA and their available follow up. Methods: The PulseRider device was implanted in 18/21 enrollments. Available core-lab adjudicated data from the first 18 implants is presented. Of those, 5 have one year follow up data available. Of the 3 device implantation failures, the locations included basilar (1), carotid terminus (1), and ACOMM (1). Results: For the 18 patients with PulseRider implanted as a coil-adjunct device, the mean age was 60.7± 8.9 yrs and 16 were female. The mean aneurysm diameter was 6.6± 2.2 mm, height 5.3±1.7 mm and neck 4.8 ±1.5 mm. Locations included the basilar apex (11), MCA bifurcation (4) and ACOMM (3). Thirteen of 18 were de novo aneurysms while the remainder (5) were treated in the setting of aneurysmal recurrence. The most common PulseRider placement was extra-aneurysmal (12/18), followed by intra-aneurysmal (4/18) and hybrid (2/18). Immediate angiographic occlusions were 66.6% RR-I, 16.7% RR-II, 16.7% RR-III. There were no device related adverse events. There were 3 (16.7%) procedure-related adverse events which did not result in neurological changes. Seven enrollments have 6 month follow up and all are RRI-II. Only 1 has one year angiographic follow up (RRI) adjudicated by the core lab, and 4 have clinical follow up (4/4 mRS 0–2). None of the target aneurysms have required retreatment. Conclusions: The results of the discontinued NAPA provide high quality data on the occlusion rates and safety profile for the PulseRider device. Further one year angiographic and clinical follow up will be reported when available. Disclosures: A. Spiotta: 1; C; Microvention. 2; C; Minnetronix, Penumbra, Cerenovus. 6; C; Cerenovus, Penumbra, Pulsar Vascular, Stryker, Microvention. K. Ebersole: None. J. Lena: None. R. Starke: 2; C; Medtronic Neurovascular, Penumbra, Cerenovus, Abbott. R. De Leacy: 6; C; Penumbra, Cerenovus, Siemens. A. Puri: 1; C; Stryker Neurovascular, Medtronic Neurovascular. 2; C; Stryker Neurovascular, Medtronic Neurovascular. D. Yavagal: 2; C; Medtronic Neurovascular, Rapid Medical, Steering Committee, Neuralanalytics. 6; C; Medtronic, Cerenovus/Johnson & Johnson, Rapid Medical, Neuralanalytics. B. Bohnstedt: 2; C; Penumbra, Stryker, Medtronic. L. Rangel-Castilla: None. A. Cheema: None. J. Davies: 1; C; National Center for Advancing Translational Sciences of the National Institutes of Health under award number KL2TR001413 to the University of Buffalo. 2; C; Medtronic, Neurotrauma Science, LLC. 4; C; RIST Neurovascular. K. de Macedo Rodrigues: None. J. Grossberg: None. B. Howard: None. C. Kellner: 1; C; Penumbra, Siemens Corp. G. Lanzino: None. S. Tateshima: 2; C; Cerenovus, Medtronic, Neurovasc, Stryker. 4; C; Neurovasc.